Branches of plant blindness and their relationship with biodiversity conceptualisation among secondary students - Pedrera, Oier; Ortega, Unai; Ruiz-González, Aritz; Diez, José Ramón; Barrutia, Oihana (Journal of Biological Education, 2021)
Although citizenship’s literacy in biodiversity is a promising way of confronting its loss, the unawareness about this topic is generalised particularly regarding plants. The latter phenomenon, named Plant Blindness (PB), not only refers to the inability to notice and identify the surrounding plants, but also to the lack of knowledge about the basics of plant biology and to the subsequent ignorance of the value of plants. Hence, the aim of this research has been to assess whether secondary students experience PB and to analyse if this phenomenon can be interrelated with their conceptualisation and attitudes towards biodiversity. For this purpose, 63 secondary students took a mixed closed- and open-ended questionnaire on different aspects of biodiversity and plant biology. The results revealed that, despite conceptualisation of biodiversity and plant literacy increased during secondary education, most students presented PB ‘symptoms’. Moreover, some of the dimensions studied were interrelated, such as comprehension of biodiversity and different aspects of plant knowledge. Therefore, these results indicate that PB has multiple branches which are not only related to plant topics sensu stricto, but also include biodiversity; which can provide novel insights into the appropriate approach to the plant blindness issue from an educational perspective.